Performance of a weakly consistent wireless web access mechanism. - Chang, Ming Feng (Sigmetrics :performance evaluation review.)
In wireless web information access, long response may be experienced. To reduce the response times of wireless data access in a mobile network, caches are utilized in the wireless handheld devices or wireless proxy server. This paper proposes a wireless web data access algorithm for WAP (wireless application protocol) caching proxy to speed up data access. Our algorithm utilizes the access frequency to tune the data expiration time. The performance of the algorithm is investigated and is compared with existing TTL-based algorithms. Our study indicates that good performance is expected for the new algorithm.